The Relationship Between Short Chain Fatty Acids and Menarche in Elementary School Students in Padang City - Zulfiqar MS; Haviz Yuad; Husna Yetti; Defrin Defrin; Ferdinal Ferry; Mondale Saputra (Andalas Obstetrics And Gynecology Journal, 2026)
Introduction: Early menarche is associated with long-term health problems. Currently, adolescent girls are increasingly experience the change of menarche age. Short chain fatty acids (SCFA) are known to play a role in the early release of GnRH which induces an earlier onset of menarche. However, so far there have been no human studies assessing SCFA levels in individuals with early menarche. Method: This is a case-control study in elementary school students in Padang which conducted from July 2024 to November 2024. The sample was all elementary school students in Padang who met the inclusion and exclusion criteria. The data collected were demographic data and SCFA levels measured in faecal samples using the ELISA method. Bivariate analysis was performed using the unpaired T-test. Result: In this study, there were 25 students with early menarche and 25 normal students. Students with early menarche experienced the earliest age of menarche in 9 years old, 56% had excessive BMI, 20% had mother history of early menarche, 20% were born prematurely, 52% had  high-fat diet, 100% lived with their parents and had no history of pornography exposure. This study found the differences in fecal SCFA levels based on age of menarche with the mean SCFA levels found to be higher in the early menarche group compared to normal menarche (39.09 ±  6.64 vs 26.91±5.01 μmol/gram; p=0.000) Conclusion: This study found the differences in fecal SCFA levels based on age of menarche